Identification and Differentiation of Closely Related Members of Bacillus cereus Group by Multiplex PCR - Roy, Sushmita; Saha, Avirup; Khan, Shafayet Imtiaze; Hasan, Md Mahmud; Karim, Muhammad Manjurul; Akhter, Marufa Zerin; Hoq, Md Mozammel; Khan, Shakila Nargis (Bangladesh Journal of Microbiology, 2023)
Highly similar genetic and phenotypic traits of at least eight bacterial species forming the ‘Bacillus cereus group’ create their precise identification and differentiation quite difficult. The present study explores the applicability of a previously suggested multiplex-PCR method for the accurate identification of the candidate Bacillus species. Out of the 257 Bacillus isolates collected from soil, 44 were identified as B. thuringiensis and 39 as B. cereus by chromogenic cultural method using Bacillus agar, although few of them shared similar colony characteristics. Identification by the multiplex PCR in a thermo cycler using 5 different sets of primer-pairs, however produced distinct amplification corresponding to the bacterial species. Four of those pairs, named BMSH, BCJH, BTJH and BASH were designed based on gyrB gene that produced amplicons of four different sizes: 604, 475, 299 and 253 bp and were specific for B. mycoides, B. cereus, B. thuringiensis, and B. anthracis respectively. The remaining one of the sets was used as an internal control which was a universal primerpair, BCGSH, designed targeting a housekeeping gene, groEL that could produce an amplicon of 400 bp in polymerase chain reactions for all members of the B. cereus group, When probing the chromosomes extracted from 257 Bacillus isolates by multiplex PCR; 48, 39 and 5 were identified as B. thuringiensis, B. cereus, and B. anthracis respectively, however the rest of the isolates did not any amplification. Interestingly, the phylogenetic tree, constructed based on partial sequences of 16S rRNA genes of selected isolates including the reference strain of B. thuringiensis (HD-73, sotto) could not differentiate the species, instead posited those in a single cluster. The multiplex PCR, therefore, proved to be a sensitive and reliable method for the identification of the bacterial candidates of Bacillus cereus group than that of cultural and rRNA gene sequence analyses. Bangladesh J Microbiol, Volume 39, Number 1, June 2022, pp 21-29